Massive expanding hematoma of the chin following blunt trauma - K Thanvir Mohamed Niazi; Dharmesh Kumar Raja; R Prakash; V R Balaji; D Manikandan; G Ulaganathan; R Yoganandha (Wolters Kluwer Medknow Publications, 2016)
Posttraumatic hematoma of the face is common and usually self-limiting in nature. We report an unusual massive expanding hematoma of the chin within 9 h following a blunt trauma with no associated injuries or fracture.